Record of Argyrodiaptomus bergi (Crustacea: Copepoda: Calanoida) after 36 years and first record in Brazil - Perbiche-Neves, Gilmar [UNESP]; Previattelli, Daniel; Nogueira, Marcos Gomes [UNESP] (Sociedade Brasileira de Zoologia, 2011)
The first record of Argyrodiaptomus bergi (Richard, 1897) from a small roadside pool at high altitude in the southern region of Brazil is presented. This is the ninth record of this species in South America (previously known from Argentina and Uruguay) since its original description, and a new occurrence after 36 years, extending its known distribution to the northeast. The environments where this species was found differ sharply, and possible explanations include the loss of habitat, high species selectivity or deficient sampling efforts. An additional description is provided, with scanning electron microscopy (SEM) photomicrographs and line drawings. Similarly to other species of Argyrodiaptomus, such as Argyrodiaptomus falcifer (Daday, 1905), Argyrodiaptomus denticulatus (Pesta, 1927) and Argyrodiaptomus granulosus (Brehm, 1933), this species shows a restricted distribution in the lower stretches of the Paraná and Uruguay rivers, particularly in small pools. The importance of better understanding the dynamics and diversity of small water bodies is discussed.
Keywords: New record; rare species; Santa Catarina